2021
DOI: 10.3389/fmicb.2021.777473
|View full text |Cite
|
Sign up to set email alerts
|

Sinking Rate and Community Structures of Autumn Phytoplankton Responses to Mesoscale Physical Processes in the Western South China Sea

Abstract: To examine the influence of mesoscale eddy on the natural phytoplankton community and its sinking rate changes, a comprehensive investigation cruise was carried out in the western South China Sea in autumn 2016. A total of 108 phytoplankton species were found, which belong to 54 phytoplankton genera; most of them were dominated by Dinophyta (54 genera), followed by Bacillariophyta (50 genera), Cyanophyta (3 genera), and Chrysophyta (1 genus). Bacillariophyta and Dinophyta were the main phytoplankton communitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 52 publications
1
3
0
Order By: Relevance
“…The ratio of diatoms to dinoflagellates is positively correlated with the sinking rates of phytoplankton in our study, which agreed with a previous investigation reported by Pitcher et al [10], who found that the sinking rate was lower when dinoflagellates rather than the diatoms were the dominant species. In fact, when diatoms bloom, their sinking rate often increases significantly.…”
Section: Coupling Of Phytoplankton Sinking Rates With Environmental F...supporting
confidence: 93%
See 1 more Smart Citation
“…The ratio of diatoms to dinoflagellates is positively correlated with the sinking rates of phytoplankton in our study, which agreed with a previous investigation reported by Pitcher et al [10], who found that the sinking rate was lower when dinoflagellates rather than the diatoms were the dominant species. In fact, when diatoms bloom, their sinking rate often increases significantly.…”
Section: Coupling Of Phytoplankton Sinking Rates With Environmental F...supporting
confidence: 93%
“…More detailed studies on phytoplankton's sinking rate should examine other factors, such as phytoplankton cell density, cell physiological activity measurement, and sea water characteristics. Some environmental factors, such as nutrient concentration, irradiance, water viscosity, and turbulence, also indirectly affect the sinking rates [8,10].…”
Section: Introductionmentioning
confidence: 99%
“…To determine the sinking rate of infected cells, A. anophagefferens CCMP1984 was infected with K. quantuckense at an MOI of 100 either 2 h (early infection) or 16 h prior (late infection) to sinking rate assessment. Sinking velocity (Ψ) was calculated using the following formula: In which βs is total exported cells, βt is total cells in the column, l is distance traveled in meters, and T is time in hours (Bienfang, 1981; Mao et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…In which 𝛽𝑠 is total exported cells, 𝛽𝑡 is total cells in the column, 𝑙 is distance traveled in meters, and 𝑇 is time in hours (Bienfang, 1981;Mao et al, 2021).…”
Section: Determination Of Vertical Transport Ratesmentioning
confidence: 99%